Pengaruh Penggunaan Bahasa Indonesia dalam Standar Akuntansi terhadap Pemahaman Standar dan Persepsi Profesionalisme Mahasiswa Akuntansi - Meilina Widya Dali; Muhammad Rizky Utia; Siti Nurhayati Domili; Siti Roihanah Kabirang; Mutia Hafiz Abas; Radiva Dwi Salmatia Pakudu; Alfiyah Nurinda Gobel; Jeremi George Billy Ponto; Aurora Fadilah Tjepah; Bilqis Fatima Abd. Rahman; Muhammad Alfarisy Putra Kasim; Anggriana Behned; Natasya Isra Rasjid; Dea Moiyo (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
Language plays an important role in the academic and professional world, particularly as a means of conveying concepts, standards, and practices. This study aims to analyze the effect of using Indonesian on the understanding of accounting standards and the professionalism of accountants. The research method used is a quantitative approach with a correlation survey method. Data collection techniques were carried out through questionnaires distributed to 17 accounting students at Gorontalo State University. Data analysis techniques included validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results of the study indicate that clear, standard, and grammatically correct language can make it easier for students to understand the concepts, principles, and application of accounting standards. Thus, the use of proper Indonesian in accounting standards has a positive impact on the understanding of accounting standards and the professionalism of accountants.